KREATIVITAS PESERTA DIDIK PADA MASA PEMBELAJARAN TATAP MUKA TERBATAS MELALUI MADING DI SMAN 1 XIII KOTO KAMPAR - Ressi Yunelda; Maria Erna; Vira Hardiani (JURNAL MANAJEMEN PENDIDIKAN, 2022)
Mading school is one of the simple media that can be used by school residents as a means of information, entertainment media, increase social insight, and develop creativity. This study aims to describe the creativity of students of SMAN 1 XIII Koto Kampar in filling out the mading in limited face-to-face learning starting in early September 2021. The method used in this study is a descriptive method with a qualitative approach and data collection through interviews and direct observation. The results of this study indicate that the creativity of students in producing wall magazines in limited face-to-face learning is very good and interesting. Mading is very effective in developing the creativity of students.